The Relationship Between Work Engagement And The Dimensions Of Nurse Staffing With Patient Safety Culture In The Inpatient Room Of Porsea Hospital - Dosmaida Nababan; Tumpal Manurung; Krista Hutapea (CV. AFDIFAL MAJU BERKAH, 2023)
Nurses play a key role in improving patient safety culture due to their continued presence around patients. Nurse performance in implementing a patient safety culture is influenced by the level of nurse work engagement. A low patient safety culture can also occur as a result of inadequate nurse staffing. This study aims to analyze the relationship of work engagement and dimensions of nurse staffing with patient safety culture at the inpatient room of RSU Porsea. The method used in this study is quantitative with a cross sectional approach. Sampling techniques used are a purposive sampling of 64 respondents. The data analysis used is Chi-Square test. The results of this study showed an overview of the level of work engagement in nurses which 21 nurses (32.8%) include in high category and 43 nurses (67.2%) in low category. The staffing dimensions revealed that 31 respondents (48.4%) answered appropriate and 33 respondents (51.6%) answered inappropriate. This study also proved that 48.4% of patient safety culture is in positive category and 51.6% is in negative category. There is a significant relationship between work engagement (p value = 0.001) and nurse staffing dimension (p value = 0.001) with patient safety culture. Hospital management is expected to provide recognition and appreciation to nurses, as well as improve the management of nurse staffing so that work engagement in nurses can be enhaced which make the application of patient safety culture can be more optimal.